Exploration of Systemic Barriers to Tef Research and Development in Central Ethiopia: A Coupled Structural-Functional Innovation Systems Analysis - Mekonnen Hailu; Degefa Tolossa; Anteneh Girma; Belay Kassa (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Over the years, there has been a continuous increase in the demand for tef (Eragrostis tef (Zucc.) Trotter) due to population growth, average incomes and urbanization in Ethiopia, but its innovation system has not been fully explored. This research aims to determine the supportive effect of tef innovation system on its investigation and development as well as the systemic constraints in the process. A coupled structural-functional innovation system analysis was used to explore the barriers faced in Central Ethiopia. The results revealed the constraints affecting the innovation system, namely limited capacity of existing actors, weak interactions and partnerships among actors, weak enforcement of institutions as well as inadequate/poor infrastructure. They also showed that technology development, technology diffusion, entrepreneurial activities, market development, resource mobilization and legitimacy creation have been the weak functions of tef innovation. Furthermore, a failure in one of the functions has a knock-on effect on others, which causes an overall dysfunctional innovation system. Based on the results, failures of the structural elements along with weaknesses of functions have constrained the development of tef innovation systems sector. A combination of technological, institutional and technical intervention must be implemented to overcome this problem.